2020
DOI: 10.1016/j.ctro.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The value of tumor-stroma ratio as predictor of pathologic response after neoadjuvant chemoradiotherapy in esophageal cancer

Abstract: HighlightsScoring the tumor-stroma ratio is a simple and reproducible method.Tumor-stroma ratio and response to neoadjuvant chemoradiotherapy are correlated.Stroma-low tumors are likely to respond better to neoadjuvant chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 38 publications
3
31
2
Order By: Relevance
“…Our study evaluated TSR on preoperative diagnostic biopsy sections of rectal cancer. Likewise, in digestive tract tumours, the results of oesophageal cancer research are consistent with our research [ 7 , 15 ]. They found that the TSR can predict the response to nCRT in oesophageal cancer patients, but they assessed the TSR in artificially selected areas by visually subjective semi-quantitative scoring (10, 20%, ..., 100%).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study evaluated TSR on preoperative diagnostic biopsy sections of rectal cancer. Likewise, in digestive tract tumours, the results of oesophageal cancer research are consistent with our research [ 7 , 15 ]. They found that the TSR can predict the response to nCRT in oesophageal cancer patients, but they assessed the TSR in artificially selected areas by visually subjective semi-quantitative scoring (10, 20%, ..., 100%).…”
Section: Discussionsupporting
confidence: 92%
“…Our study adopted a full quantification method on WSIs in LARC patients. Compared with the results from Pelt et al (Kappa = 0.73) [ 7 ], our method achieved a higher degree of agreement for TSR evaluation (ICC = 0.99). Furthermore, the multivariate analysis uncovered that only the TSR, neoadjuvant radiotherapy dose and FOLFOX regimen were independent predictive factors.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations